2013
DOI: 10.1074/jbc.m113.470146
|View full text |Cite
|
Sign up to set email alerts
|

Non-receptor-tyrosine Kinases Integrate Fast Glucocorticoid Signaling in Hippocampal Neurons

Abstract: Background: The intracellular signaling cascades through which corticosterone rapidly alters neuronal activity are poorly defined. Results: Corticosterone alters glutamatergic transmission by activating diverse GPCR-dependent signaling pathways. Conclusion: Corticosterone-induced changes in neuronal excitability are initiated at the plasma membrane. Significance: The sequential recruitment and integration of diverse signaling cascades by corticosterone adds to the understanding of how steroids rapidly alter ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
3
28
0
Order By: Relevance
“…Consistent with reports in other systems (41), glucocorticoids alone induced Src phosphorylation in AtT-20 cells. Although corticosterone and CRH which have converse effects of ACTH secretion had similar effects of Src phosphorylation, the facts that corticosterone prevented the early effect of CRH on Src phosphorylation, and that Src inhibitors inhibited CRH-stimulated ACTH secretion, suggest that inhibition of Src phosphorylation contributes to the rapid inhibitory effect of glucocorticoids on CRHstimulated ACTH secretion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with reports in other systems (41), glucocorticoids alone induced Src phosphorylation in AtT-20 cells. Although corticosterone and CRH which have converse effects of ACTH secretion had similar effects of Src phosphorylation, the facts that corticosterone prevented the early effect of CRH on Src phosphorylation, and that Src inhibitors inhibited CRH-stimulated ACTH secretion, suggest that inhibition of Src phosphorylation contributes to the rapid inhibitory effect of glucocorticoids on CRHstimulated ACTH secretion.…”
Section: Discussionsupporting
confidence: 91%
“…While the reversibility of electrophysiological effects of glucocorticoids by intracellular application of the guanyl nucleotide binding protein (G-protein) inhibitor, GDP-␤-S (40), or pertussis toxin (31,41) has suggested a G-protein coupled membrane receptor, other in vitro (30) and in vivo (42) studies have showed rapid glucocorticoid-induced inhibition of ACTH secretion reversible by a GR antagonist, concluding that the effect is mediated by the classical GR. The present experiments show complex actions of RU486, clearly blocking the early inhibitory effect of corticosterone but having a late inhibitory effect on CRH-stimulated ACTH secretion on its own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PYK2 is a component of the NMDAR complex (35) and is activated by NMDAR stimulation (36). In addition, a rapid response of hippocampal neurons to glucocorticoids includes activation of Pyk2 via a putative G-protein-coupled receptor (19). We show here that the subcellular distribution of activated Pyk2 (phospho-Y402 Pyk2) in hippocampal pyramidal neurons is altered in chronically stressed mice.…”
Section: Discussionmentioning
confidence: 79%
“…Hippocampal neurons respond rapidly to glucocorticoids via a G-protein-coupled membrane receptor, and downstream effectors include activation of Pyk2 (19). Activation and nuclear translocation of Pyk2 also has been observed in cultured cells treated with pervanadate [protein tyrosine phosphatase inhibitor (20,21)] and in hippocampal slices treated with depolarizing concentrations of K + (22).…”
Section: Decreased Nup62 Content In Hippocampal Neurons Exposed To Chmentioning
confidence: 99%